Transfusion associated CMV infection: Transfusion strategies for high risk patients (Bangladesh Journal of Medical Microbiology, 2012)
The role of blood and blood products in acquisition of cytomegalovirus (CMV) infections following transfusion was reviewed in this study. CMV IgG prevalence was particularly high in Bangladesh. Thus 97% of the study groups were found to be CMV IgG positive. The present study showed that CMV IgM antibody prevalence was significantly higher in multiple transfused groups (24%) than control group (2%) indicating CMV primary infection and reactivation or reinfection occur frequently in multitransfused patients. Most CMV infections acquired after transfusion are either asymptomatic or characterized by a self-limited infectious mononucleosis syndrome but it may be serious or fatal in those who are immunocompromised. Particularly at risk are low-birth weight infants, bone marrow and organ transplant patients. If a patient is at high risk of getting CMV diseases, blood from seronegative donors is appropriate and likely to prevent post transfusion CMV infection. Alternatively, blood that has been filtered to decrease the number of white blood cells - the cells that carry CMV - will protect patients from getting a CMV infection from transfusion.DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10828